Clinical Predictors of Abnormal Computed Tomography Findings in Mild Head Injury - Yogi, Nikunj; Karmacharya, Balgopal; Gurung, Amrit (Nepalese Journal of Radiology, 2018)
Introduction: Whether to scan a minor head injury with Glasgow Coma Scale (GCS) 15 who appears well and has a normal physical and neurological exam or not is an issue commonly faced in all emergency departments. In this study, we tried to assess the predictability of clinical parameters in predicting traumatic intracranial lesions in Computed Tomography (CT) scans of patients with minor head injuries with GCS 15. Methods: A prospective observational study was carried out in between January to December 2016 in Manipal Teaching Hospital, Pokhara, Nepal. Various clinical predictors of 415 cases of minor head injury with GCS 15 were assessed to see if they could predict the abnormal CT scans in these cases. Clinical variables found significant in bivariate analyses were further analyzed using logistic regression to calculate the odds of each variable to detect abnormal CT scans. Results: There were 119 (28.7%) abnormal CT scans in the study. Vomiting, LOC (Loss of Consciousness), seizure and headache were the significant predictors of abnormal CT scans with an odds of 4.254 (95% CI: 2.373-7.627), 2.396 (95% CI: 1.258-4.562), 5.803 (95% CI: 1.110-30.336) and 1.967 (95% CI: 1.008-3.839) respectively Conclusion: Vomiting, LOC, seizure and headache are important clinical predictors of abnormal CT scan in cases of minor head injuries with GCS 15.